Edukasi Pajak Pada Usaha Angkringan dan Warkop di Kecamatan Cikarang Pusat - Tikaromah, Oom; Yuningsih, Nining; Prasetyo, Bayu; Sahirah, Anisa Maulidatus; Ardiyan, Ardiyan (DPPM Universitas Pelita Bangsa, 2024)
Cikarang Pusat sub-district is one of the areas with economic growth driven by the presence of small and medium enterprises, including Angkringan and Warkop businesses. However, business actors' understanding of tax obligations is still shallow. This activity aims to provide tax education to partners to increase their tax awareness and compliance. The method used includes an initial survey to identify the level of understanding and educational needs, and implementation is carried out through direct assistance in the field. The results of the activity showed a significant increase in business owners' awareness and understanding of taxation knowledge after participating in the education programme. Before the programme, partners had an average knowledge of 45% regarding taxation, while after the programme, this figure increased to 85%. Continued education and support from the government and related organisations are needed to ensure the sustainability and positive impact of this programme.